Challenges and opportunities for transportation services in the post-COVID-19 era - Catenazzo, Giuseppe, 1982- (Advances in hospitality, tourism, and the services industry book series., 2022)
"This book provides a timely contribution to transportation management to explore the challenges and the new directions to match travelers' needs in a post-COVID19 era with the aim of offering methodological applications in transportation to inspire scholars to further their efforts in boosting the design and use of sustainable mobility"--